An examination of students’ perceptions of class discussions in ‘Malay Language for Professional Communication’ - Hadayat Rahmah Hasan,; Yamimi Turiman,; Salwa Othman,; Zaamah Mohd Nor, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2021)
Class conversation is a beneficial mechanism that involves students’ listening, thinking, and speaking abilities. It is a tool used in most language classes to promote student involvement and solicit their feedback, allowing them to improve their comprehension of the lesson. While this student-centred method has its advantages, having students to actually engage in a debate can be difficult. This may be attributed to a lack of enthusiasm and curiosity among students, as well as language incompetency, to list a few factors. The aim of this study is to discover out how students feel about engaging in class discussions and voicing their agreement and dissatisfaction using the English language as the tool of instruction. The participants in this research are first-semester Malay Language for Professional Communication students. These students are majoring in Malay Language Studies, and they are required to take the English for Oral Presentation course as part of their degree requirements. This comprehensive research discovered that students’ perceptions of engaging in class debates, as well as voicing consensus and opposition, were relatively poor to medium. Their negative impression suggests that the students could be confronted with barriers that prevented them from having productive class discussions. The findings of this research would have important consequences on how class discussions are used in language classrooms.